Hazardous aerosol emissions during agriculture biomass burning season in Son La and Ba Vi regions, Vietnam - Popovicheva, Olga B.; Eleftheriadis, Konstantinos; Engling, Guenter; Anh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2017)
Major national emission sources are assessed by characterization of smoke pollution arising due to traditional agriculture, domestic, and cooking activities in the regions of the biggest biomass burning. Measurement campaigns were carried in Son La and Ba Vi regions, Vietnam, during the dry seasons of 2013 and 2015-2016. PM and BC monitoring, aerosol sampling, chemical speciation were conducted to evaluate ambient smoke level, to relate the characteristics of local on-field emissions to regional aerosols, and to identify the dangerous components of smoke composition. The regions Son La and Ba Vi in February-June faced severe levels of air pollution, with critical PM2.5 and PM10 concentrations up to 130 and 167 µg/m3, respectively, significantly exceeding the air quality standards. A wide range of PM mass concentrations was categorized according to the smoke level, supported by the evolution of carbon (OC, EC) fractions as well as ionic species and molecular markers. The level of PM and BC concentrations was seen to be dependent on factors such as weather conditions and precipitation. Non-acid carbonyls, carboxylates, and aliphatic carbon compounds were evolved with increasing smoke intensity, together with carbonates in coarse size fractions, indicating a large impact of smoke emissions and soil lifted up by the intense fires. On-field emissions in both smoldering and flaming phases were assessed in near-source measurements.